Efektivitas Komunikasi Dalam Berdakwah Ustadz Hanan Attaki Dalam Akun Instagram Terhadap Spiritualitas Generasi Z - Rejeki, Tri; Razzaq, Abdur; Nugraha, Muhammad Yudistira (Komunika : Jurnal Ilmiah Komunikasi, 2024)
Hanan Attaki through his Instagram account @hanan_attaki and its influence on the spirituality of Generation Z. The research employs a descriptive qualitative approach, with data collected through content observation, literature review. The findings indicate that da'wah communication delivered in a visual, emotional, and contextually relevant manner fosters psychological closeness and enhances spiritual awareness among youth. Content centered on themes such as love, anxiety, self-discovery, and worship motivation received the most positive engagement. Casual language, modern visual aesthetics, and interactive responses in the comment section serve as key factors in the success of Ustadz Hanan Attaki's da'wah communication. This study affirms that social media can be an effective da'wah platform for younger generations when applied through adaptive and contextual communication strategies.